Evaluation of Tourism Potential Development Policy in Togean Islands, Tojo Una Una Regency - Indrawijaya, Indrawijaya (International Journal Papier Public Review, 2020)
The purpose of this study was to determine the extent to which the development of tourism potential based on the aspects of tourism attraction and promotion, human resources and institutions, the environment, as well as aspects of tourism accessibility and facilities. This study uses a qualitative method with a phenomenological approach to describe, analyze and interpret the implementation of programs / activities from various aspects of tourism development. The theory used in this research is William Dunn's policy evaluation theory with the criteria of effectiveness, efficiency, sufficiency, leveling, responsiveness, and accuracy. Research results The development of tourism attractions and promotion is not in line with the concept of sustainable development and the image of the Togean Islands as a new ecotourism destination. The development of community empowerment, research and education on ecosystems, as well as improving the human resources of tourism actors have not run optimally in accordance with the potential of natural tourism. Programs / activities for the protection, supervision and management of priority tourist destinations, especially those that have the appeal of snorkeling and diving, have not been implemented optimally so that illegal fishing activities and waste problems cannot be resolved properly. The priority of developing transportation access for tourists is not appropriate and uneven in order to respond to the needs of tourist visits to priority tourist destinations.